SENTENCE PATTERN ANALYSIS OF ACTIVE AND PASSIVE CONSTRUCTIONS IN A NEWS ARTICLE: A TRANSFORMATIONAL–GENERATIVE GRAMMAR PERSPECTIVE ON “DEADLY STROMS RAVAGE ASIA, KILLING MORE THAN 600” - Devi meilia permata sari; Aisyah Kusuma Wardani; Abdul Syukur; Sigit Wibowo; Eny Maulita Purnama Sari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2026)
Abstract: This study uses Noam Chomsky's Transformational–Generative Grammar to examine phrase patterns in a news item, with an emphasis on the distribution of active and passive constructs at the surface structure level. The information came from an Egypt Independent news item headlined "Deadly Storms Ravage Asia, Killing More Than 600 with Hundreds Missing." This study used a qualitative descriptive method to identify 40 sentences that were carefully categorized into passive patterns (S–V–O–Actor and S–V–C–Actor) and active patterns (S–V–O, S–V–O–C, and S–V–C). A thorough analysis of how syntactic structures are implemented in news discourse and how surface sentence patterns represent the communicative objectives of journalistic writing is made possible by this classification.The results show that active sentence structures predominate in the news story under analysis, with the S–V–O pattern occurring most frequently, followed by the S–V–C pattern, and the S–V–O–C pattern occurring less frequently. This dominance implies that direct reporting of events and actions is given priority in the news content, making it simple for readers to identify agents, procedures, and impacted businesses. Passive constructs, on the other hand, are less common and are mostly employed to highlight victims, results, or effects of events rather than the agents. This is consistent with journalistic techniques to preserve neutrality and concentrate on impact. These results are in line with Abdul-Munem's (2025) research, which contends that active voice constructs are more common than passive ones in news writing because they offer efficiency, clarity, and immediacy. From a transformational generative standpoint, the preference for active surface structures shows that thw communicative demands of conveying factual occurrences functionally inspire and affect syntactic choices in new discourse.